Identification of Tree Species and Their Potential as Carbon Stock in Three Urban Forests of Malang City, Indonesia - Dwi Suheriyanto; Gita Niken Madapuri; Didik Wahyudi (Biota, 2024)
This study aims to identify tree species and their potential as carbon stock in three urban forests of Malang City. This research was conducted in three urban forests including the Urban Forest of Malabar, Velodrome, and Hamid Rusdi. Data were analyzed with an important value index (IVI) and Carbon stock estimation. There were 41 species of trees in three Malang City Forests. There are differences in tree dominance in the three Malang city forests, namely: the Malabar city forest is Albizia chinensis, the Velodrome city forest is Gmelina arborea, and the Hamid Rusdi city forest is Polyalthia longifolia. The highest value of carbon stock in the Malabar urban forest is A. Chinensis, 6,214.38 kg; in the Velodrome urban forest is Enterolobium cyclocarpum, 7,225.88 kg; and in the Hamid Rusdi Urban Forest is Samanea saman with a carbon stock of 4,757.01 kg.